1997
DOI: 10.1007/s002560050230
|View full text |Cite
|
Sign up to set email alerts
|

Benign giant cell tumor of bone with osteosarcomatous transformation (”dedifferentiated" primary malignant GCT): report of two cases

Abstract: It is not uncommon for sarcomatous transformation of giant cell tumor (GCT) of bone to occur after radiation, but rarely does malignant transformation occur spontaneously, with less than 15 cases reported up to 1995. Only four of these cases have been documented in detail. We report two additional cases of GCT of bone spontaneously transforming or "dedifferentiating" into osteosarcoma without radiation therapy. The first case is absolutely unique and most interesting in that the dedifferentiation process occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 29 publications
0
56
0
3
Order By: Relevance
“…27 Bertoni F et al 28 reported 6 cases of post surgical secondary malignant GCT without prior irradiation. They also mentioned that the average interval between benign GCT and sarcoma diagnosis of these patients was 18 years, much longer than the average interval observed in patients who received previous radiotherapy (9 years).…”
Section: Discussionmentioning
confidence: 99%
“…27 Bertoni F et al 28 reported 6 cases of post surgical secondary malignant GCT without prior irradiation. They also mentioned that the average interval between benign GCT and sarcoma diagnosis of these patients was 18 years, much longer than the average interval observed in patients who received previous radiotherapy (9 years).…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent evidence suggests that spontaneous malignancy in giant cell tumors most certainly represents a form of dedifferentiation. 12,13 When malignant transformation of a benign giant cell tumor occurs, it usually presents as a fibrosarcoma or OS. 11 One of our cases initially was diagnosed by FNAB as a giant cell tumor.…”
Section: Discussionmentioning
confidence: 99%
“…After intralesional or even marginal excision, it locally recurs in 20% to 40% of cases [39], and in less than 5% of cases, GCT may develop histologically benign metastases [3]. GCT may also spontaneously undergo sarcomatous transformation [5], the risk of progression being greatly increased by radiation [6]. The outcome of this lesion cannot be predicted on the basis of histologic or radiographic criteria [9,23], and in the absence of a clear histogenetic origin, GCT is currently classified among lesions with an uncertain derivation and named after its peculiar morphologic appearance.…”
Section: Introductionmentioning
confidence: 99%